Hot Very Small dust Grains in NGC 1068 seen in jet induced structures thanks to VLT/NACO adaptive optics - Rouan, D; Lacombe, F; Gendron, E; Gratadour, D; Clenet, Y; Lagrange, A; Mouillet, D; Boisson, C; Rousset, G; Mugnier, L; Thatte, N; Genzel, R; et al. (2003)
We present K, L and M diffraction-limited images of NGC 1068 obtained with NAOS+CONICA at VLT/YEPUN over a 3.5" field around the central engine. Hot dust (Tcol = 550-650 K) is found in three different regions : (a) in the true nucleus, seen as a slightly NS elongated, core of extremely hot dust, "resolved" in K and L with respective diameters of ~5 pc and 8.5 pc ; (b) along the NS direction, as a "spiral arm" and a southern tongue ; (c) as a set of parallel elongated nodules ("wave-like") bracketting the jet. Several structures observed on radio maps, mid-IR or HST UV-visible maps are seen, so that a precise registration can be done from UV to 6 cm. These results do support the current interpretion that source (a) corresponds to emission from dust near sublimation temperature delimiting the walls of the cavity in the central obscuring torus. Structure (b) is thought to be a mixture of hot dust and active star forming regions along a micro spiral structure that could trace the tidal mechanism bringing matter to the central engine. Structure c)which was not known, exhibits too high a temperature for "classical'' grains ; it is most probably the signature of transiently heated very small dust grains (VSG) : "nano-diamonds", which are resistant and can form in strong UV field or in shocks, are very attractive candidates. The "waves'' can be condensations triggered by jet induced shocks, as predicted by recent models. First estimates, based on a simple VSG model and on a detailed radiative transfer model, do agree with those interpretations, both qualitatively and quantitatively.